Aaron Copland - Venezia, Mike (2018)
"Clever illustrations and story lines give children a light yet realistic overview of this composer's life and style and music" -- Amazon.com.
Includes bibliographical references and index.
7-9
Keywords: Copland, Aaron, -- 1900-1990 -- Juvenile literature; Composers -- United States -- Biography -- Juvenile literature